Air drying technique for cytogenetic studies in freshwater planarians (Platyhelminthes) - Margaría, Cecilia Beatriz (1997)
Fil: Margaría, Cecilia Beatriz. Facultad de Ciencias Naturales y Museo; Universidad Nacional de La Plata